Deletion of GIRK2 subunit containing GIRK channels of neurons expressing dopamine transporter decrease immobility time on forced swimming in mice. (5th February 2018) - Honda, Ikutaro; Araki, Kimi; Honda, Sokichi; Soeda, Fumio; Shin, Min-Chul; Misumi, Shogo; Yamamura, Ken-ichi; Takahama, Kazuo
Highlights: Generation of GIRK2 cKO mice with specific deletion of GIRK2 subunit in neurons expressing dopamine transporter. GIRK2 cKO mice reduced depression-like behaviours. GIRK2 cKO mice mimic the effects of antitussives in the forced swimming. Abstract: We previously reported that non-narcotic antitussives possessing inhibitory actions on G protein-coupled inwardly rectifying potassium (GIRK) channels have antidepressant-like effects in the forced swimming test in normal and adrenocoticotropic hormone (ACTH) treated rats. Furthermore, the antidepressant-like effects of the antitussives such as tipepidine were blocked by dopamine D1 receptor antagonist, and inhibitory actions on GIRK channels of dopamine neurons may be involved in the antidepressant-like effects of tipepidine. In this study, we generated GIRK2 DAT KO mice with Girk2/Kcnj6 conditional deletion and assessed depression-related behavior of the mice. The Cre/ loxP system was used to selectively delete GIRK2 subunit containing GIRK channels in the neurons expressing dopamine transporter. First, deletion of GIRK2 subunits in the ventral tegmental area (VTA) neurons expressing dopamine transporters was confirmed by hisitochemically and electrophysiologically. In the mice, a significant decrease in the immobility time of forced swimming test was observed. Locomotor activity of the mice was not changed compared to that of GIRK2 floxed mice, when tested in the open field. These results suggest that the antidepressant-like effect of antitussives such as tipepidine may be caused partly through the inhibitory actions on GIRK channels in the dopamine neurons.